Molecular modeling investigation of para-nitrobenzoic acid interaction in β-cyclodextrin - Leila Nouar; Sakina Haiahem; Abdelazize Bouhadiba; Fatiha Madi; Leila Lagrate (My University, 2011)
Geometry optimizations of para-nitrobenzoic acid (PNBA)/β-cyclodextrin complex were carried out using MM+, PM3 and density function theory B3LYP/6-31G*. Calculations were performed upon the inclusion complexation of β-cyclodextrin (CD) with neutral (PNBA1) and anionic (PNBA2) species of para-nitrobenzoic acid. The results obtained from both methods consistently indicate that the complex of PNBA2/β-CD (B) is significantly more favorable than the others energetically. The negative enthalpy changes calculated from the statistical thermodynamic calculation suggest that both the inclusion complexation is favored enthalpy-driven process. The geometry of the most stable complex shows that the aromatic ring is deeply self-included inside the hydrophobic cavity of β-CD and also intermolecular hydrogen bonds were established between host and guest molecules. This suggests that hydrophobic effect and hydrogen bond play an important role in the complexation process.